Monte Carlo Simulation Approach to Determine the Optimal Solution of Probabilistic Supply Cost - Ramadan, Helmi; Gio, Prana Ugiana; Elly Rosmaini (Talenta Publisher, 2020)
Monte Carlo simulation is a probabilistic simulation where the solution of problem is given based on random process. The random process involves a probabilitydistribution from data variable collected based on historical data. The used model is probabilistic Economic Order Quantity Model (EOQ). This model then assumed use Monte Carlo simulation, so that obtained the total of optimal supply cost in the future. Based on data processing, the result of probabilistic EOQ is 486128,19. After simulation using Monte Carlo simulation where the demand data follows normal distribution and it is obtained the total of supply cost is 46116,05 in 23 months later. Whereas the demand data uses Weibull distribution is obtained the total of supply stock is 482301,76. So that, Monte Carlo simulation can calculate the total of optimal supply in the future based on historical demand data.